Integrated watershed management: a case study in Himalaya. - Sharma, E. (Nainital, 1992)
Environmental problems with multifarious implications have invariably led to consider watershed as a unit for analysis of resource base and development planning in the hills. The watershed management approach is inherent to the objective of achieving a balanced development of diverse subsistance needs of the humankind in an integrated manner rather than sectoral perspective. In order to comply with the above approach a five year study on Integrated Watershed Management was initiated by the G.B. Pant Institute of Himalayan Environment & Development through its Sikkim Unit and the work of the first two years have been compiled here. The second part will deal with management aspects. This part of the book emphasizes on physical background, demography, land use, water resource, forest, livestock, agriculture, settlement and infrastructure of a micro-watershed in south Sikkim. The data presented in this book are mainly primary and generated through extensive field and laboratory works.
Keywords: Landuse